Using the UTAUT Model to analyze e-procurement adoption in Malaysian Construction Industry/ Suhaidi Elias @ Alias - Elias @ Alias, Suhaidi (UiTM Cawangan Johor, 2018)
This paper seeks to provide further understanding of issues surrounding acceptance of e-procurement by contractors in the Malaysian Construction Industry. The Unified Theory of Acceptance and Use of Technology (UTAUT) model by Venkatesh et al. (2003) was employed to determine the strength of predictors for contractors to accept and use e-procurement. Questionnaires were administered to 115 contractors, during seminars and workshops organized by CIDB. Analysis of Moments Structures (AMOS) 24 and Statistical Package for the Social Sciences (SPSS) 24 were used to analyze the data collected. The measurement and structure model was appraised using Structural Equation Modeling. The findings show that performance efficacy, effort efficacy, social influence and facilitating condition have significant effect on e-procurement usage since the p-value for all the cases are less than 0.05. The researcher therefore recommends that future studies should include other variables to improve the variance explained by the predictors, since there are variations in the research environments.